Designing Arabic grammar exercise book for non-native speakers in Malaysia using Malay language as a medium - Mustapai, Mohd Zulhisyam; Mat Zain, Zairul; Hashim, Marzidah; Raja Sulaiman, Raja Munirah (2013)
This project aims at the design of an Arabic grammar exercise book for non-native speakers in Malaysia using Malay language as a medium. The mixed-method approach was implemented which employed techniques such as quantitative survey, interviews, content analysis, field notes and observations. This project will contribute theoretically in the form of design a new approach in Arabic grammar studies and practically in the design of suitable Arabic grammar exercise book for Malay learners in Malaysia using Malay language as a medium.